Assessing the sustainability of repetitive floor plan using Building Information Modelling-DIGITAL TWINS framework - Istanbullu Ali; Omar Emad Alabo; Aijoma Mohammed (E3S Web of Conferences)
Various factors, including the nature of the utilized equipment, labour expertise, availability of resources, and meteorological circumstances, might impact the efficiency of work on construction sites. As a result, site and planning engineers must continuously monitor and assess construction progress considering site conditions and the performance of used construction resources. In multi-storey buildings, repetitive floor construction plan impacts enormously construction site sustainability. To identify an optimal set of construction resources, this paper presents Building Information Modelling-DIGITAL-TWINs (BIMDTs) framework, which planners and site engineers can use to easily monitor and control workflow progress of the repetitive floor. Using a digital model, DTs replicate the actual workflow process on a building site and guarantee a consistent information flow. To guarantee information flow between the building site and the digital model, several communication technology tools could be deployed and tested (High-definition site construction camera, regular site monitoring using drones, infrared smart sensors, etc.). The initial results of this research show an important improvement in the sustainability of construction sites. Reduced formworks oil consumption, improved human resource safety, and increased site resource profitability were observed in several treated real cases.